On the Mukhran Machavariani’s language of poetry (word formation, dialectisms, slang) - Khvingia, Manana (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Mukhran Machavariani’s work is exceptionally intriguing from a linguistic perspective. The poet wandered deep into the heart of Georgia, tirelessly seeking out forgotten words, reviving them, and breathing new life into them. The goal of this research is to introduce readers to Mukhran Machavariani’s poetry and highlight the richness of the Georgian language within his verses. Each word is carefully considered and imbued with nuanced meaning. Machavariani assigns a special place in his work to dialects and ancient, forgotten words, using them to add different shades of color and imbue them with meaningful content. Throughout his career, the poet has collected pearls from various regions of Georgia and seamlessly weaves them into his compositions. Machavariani can be likened to an „iron man“ of words, fearlessly introducing new vocabulary and crafting them into poetic gems. The poet describes his process as a search, often uncertain of what he will find until he does, at which point the word is reborn with its own tone, sound, and sometimes even new meaning. Machavariani asserts, „It is sacrilege to approach a poetic verse solely through grammar!“ His words are renowned for their beauty, musicality, and poetic resonance, deeply embedding themselves in the reader’s consciousness from the first encounter, which he calls „Mukhrani“. Archaic words abound in Mukhran Machavariani’s poetry, which he embraces without reservation. He asserts, „A word that survives in any dialect cannot be considered archaic“, while acknowledging the need for balance amidst the influx of foreign terms. The poet does not shy away from using slang, using it to underscore his stance on various characters and actions that he finds objectionable as a citizen, poet, and individual: „When I see such villains on the TV screen, the barn floor is where they belong, having already left this world...“ Thus, the archaisms, dialects, and neologisms in Mukhran Machavariani’s poetry reflect his deep respect and commitment to the Georgian language. Understanding each word is crucial when delving into Machavariani’s poems, as they reveal the poet’s thoughts and profound love for the roots of his native language.